THE POTENTIAL COMBINATION OF CENTELLA ASIATICA, CURCUMA LONGA, AND PIPER NIGRUM EXTRACTS IN TREATING BRAIN INJURY: IN VITRO, IN VIVO AND SILICO STUDIES - ARISTIANTI; ASWAD, MUHAMMAD; ARSYAD, ARYADI; NURSAMSIAR; NUR, SYAMSU; ISLAM, ANDI ASADUL (International Journal of Applied Pharmaceutics, 2025)
Objective: Traumatic brain injury is a head injury that causes brain dysfunction. This disorder can have a bad effect if not treated quickly and appropriately. This study aims to examine the extract of Gotukola (Centella asiatica), turmeric (Curcuma longa), and black pepper (Piper nigrum) as natural medicines that can treat brain injury problems. Methods: The parameters tested in this study included testing the memory of experimental animals using the Y-Maze method, in vitro inhibition of glutaminase, and in silico research through molecular docking and molecular dynamics on the compounds of each extract that have been previously reported. Results: Each extract had activity in increasing memory, but a combination formula of the three extracts showed a significant increase in memory (p<0.05, n = 5). The combination extract of gotu kola, turmeric, and black pepper in a ratio of 50:50:50 (combination 1), 25:50:50 (combination 5), and 25:12.5:50 (combination 8) continued its activity in inhibiting glutaminase. The results showed a significant decrease in glutaminase activity when applied to the three combination extract formulas. This study is also supported by in silico results showing that the asiaticoside compound identified in gotu kola extract, 1,5-bis (4-hydroxy-3-methoxyphenyl)-1,4-pentadien-3-one compound from turmeric extract and Bacitritinib from black pepper extract have an important role in interacting with the target protein glutaminase with protein data bank 4O7D in molecular docking studies and interacting stably in molecular dynamics. Conclusion: This study has supported the development of a combination extract formula of gotu kola, turmeric, and black pepper as a candidate for treating brain injury.